STATINS AND PERCUTANEOUS CORONARY INTERVENTION. FOCUS ON THE ATORVASTATIN - N. G. Gogolashvili (Столичная издательская компания, 2015)
The possibility of atorvastatin in reducing the risk of periprocedural myocardial infarction and other cardiovascular events in patients with percutaneous coronary intervention is discussed.